The Belgian people's war : a violation of international law / translations from the official German white book, published by the Imperial foreign office. - Germany. Auswärtiges Amt. (Tufts University. Tisch Library., 2015)
1 online resource (135 pages) illustrations.; Translation of Die Völkerrechtswidrige führung des belgischen volkskriegs.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University,2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.